The Joys and Surprises of Telling Your Life Story - Kunz, John A., & Tyrrell, Mary O'Brien (University of Wisconsin Board of Regents, 2002)
Designed to inspire older adults to tell their life stories informally, in writing, on video or in public performance. Introduces the idea of working with a life story professional and offers guidelines for choosing one. Presents several older people who discuss recording their memoirs. Examines sensitive issues and potential problems in helping people record their life stories.
Contributors: Mary O'Brien Tyrrell; Association of Personal Historians; International Institute for Reminiscence and Life Review; Bi-Folkal Productions; University of Wisconsin--Superior.
Keywords: Life Review; Personal History; Life Reminiscence